Changes in the wintering distribution of Wrangel Island Snow Geese Anser c. caerulescens - Boyd, W Sean; Cooke, Fred (Wildfowl, 2000)
The long-term changes in the size of the Lesser Snow Goose (Anser c. caerulescens) population that breeds on Wrangel Island, Russia, and its associated wintering populations in North America are described. In contrast to exponential increases in almost all other populations of Snow Geese in North America, the Wrangel population declined in the 1970s and has remained relatively stable since then. The proportion of the entire Wrangel population on the Fraser/Skagit deltas (northern wintering site) increased at a rate of just over 1% per year, almost doubling since 1970. This suggests that the proportion in California must have declined at the same rate. The distribution shift may have been caused by differential emigration, survival, and/or fecundity rates among the two wintering populations. These possibilities are discussed along with what further evidence is needed to test them.